Fostering Speaking Skills and EFL Students Achievements: Teachers Voices - Octaberlina, Like Raskova; Anggarini, Ida Fitri (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research delves into the importance of oral communication skills in English as a Foreign Language (EFL) education, specifically focusing on the viewpoints and experiences of language instructors in an Indonesian Madrasah. By investigating the teaching methods employed to develop speaking proficiency in qualitative study, the study aims to uncover the connection between effective teaching approaches and enhanced spoken communication abilities among EFL students in the Madrasah in Malang, Indonesia based on the teacher voices. Utilizing observation, interviews, and document analysis, the research explores the challenges faced and innovative strategies employed by educators in the Madrasah language classroom. The findings indicate the insights provided contribute diverse perspectives to the ongoing conversation on language pedagogy, providing a comprehensive understanding of the intricate interplay between teaching practices and the advancement of speaking skills in EFL learners at the Madrasah. Also, this study has implications for shaping curriculum design, improving teacher training, and fostering the student's speaking skills and achievement such as speech and storytelling. Overall, it enhances EFL education programs.